RETRACTED ARTICLE: Establishment of an Acanthamoeba keratitis mouse model confirmed by amoebic DNA amplification - Heekyoung Kang; Hae-Jin Sohn; A-Young Park; A-Jeong Ham; Jeong-Heon Lee; Young-Hwan Oh; Yong-Joon Chwae; Kyongmin Kim; Sun Park; Hongseok Yang; Suk-Yul Jung; Jong-Hyun Kim; et al. (Scientific Reports)
Abstract Acanthamoeba castellanii, the causative agent of Acanthamoeba keratitis (AK), occurs mainly in contact lens users with poor eye hygiene. The findings of many in vitro studies of AK, as well as the testing of therapeutic drugs, need validation in in vivo experiments. BALB/c mice were used in this study to establish in vivo AK model. A. castellanii cell suspensions (equal mixtures of trophozoites and cysts) were loaded onto 2-mm contact lens pieces and inserted into mouse eyes that were scratched using an ophthalmic surgical blade under anesthesia and the eyelids of the mice were sutured. The AK signs were grossly observed and PCR was performed using P-FLA primers to amplify the Acanthamoeba 18S-rRNA gene from mouse ocular tissue. The experimental AK mouse model was characterized by typical hazy blurring and melting of the mouse cornea established on day 1 post-inoculation. AK was induced with at least 0.3 × 105 A. castellanii cells (optimal number, 5 × 104), and the infection persisted for two months. The PCR products amplified from the extracted mouse eye DNA confirmed the development of Acanthamoeba-induced keratitis during the infection periods. In conclusion, the present AK mouse model may serve as an important in vivo model for the development of various therapeutic drugs against AK.